THE RELATIONSHIP OF EMOTIONAL INTELLIGENCE AND LEARNING MOTIVATION WITH LEARNING ACHIEVEMENT IN CLASS V IPS STUDENTS IN PRIMARY SCHOOL INDONESIA - Atim Hariyadi; Miftahul Arifin (International Jurnal of Education Schoolars, 2020)
Learning achievement is one measure that students have learned well. Learning achievement is an indicator of education in schools which is the hope of all parties, namely parents, teachers, and students. Achievement is a measure of the quality of education. Learning achievement is needed in the consideration to determine class promotion, graduation, and selection of outstanding students. Optimal learning achievement is the main goal of students in learning. Learning achievement can be measured from the value obtained by students. The average score related to the social studies score of the subject teacher shows similarities. Based on the background described above, the researcher's problems can be formulated as follows: is there a relationship between emotional intelligence and learning achievement? Is there a relationship between motivation and learning achievement? And collectively, is there a relationship between emotional intelligence and learning motivation? with learning achievement ?. In accordance with the formulation of the problem, this study has specific objectives, namely: to describe the relationship between emotional intelligence and learning achievement, to describe the relationship between motivation and learning achievement; and jointly describe the relationship between emotional intelligence and learning motivation and learning achievement. Meanwhile, the long-term goal is as a reference for other researchers and this research will be included in an accredited scientific journal. This research is a study that aims to determine the relationship between emotional intelligence and learning motivation with student achievement. The type of research that researchers do is quantitative research because in the procedure and analysis the researcher uses statistical analysis. The research sites are in urban and rural elementary schools. In determining the location of SD using SD numbering, from the population list every multiple of 20 is taken as a sample. All students in grade 5 for SD will be used as respondents to fill out the questionnaire. The methods used to collect data in this study include questionnaires, documentation, observation methods, and interviews.